Study on the hydrogen embrittlement susceptibility of AISI 321 stainless steel. (April 2021) - Xiuqing, Xu; Junwei, An; Chen, Wen; Jing, Niu
Highlights: The fracture mode of specimen after EHC changed from ductile fracture to brittle fracture. The hydrogen cracks are preferentially appeared at grain boundaries, inclusions and interface. The transformation and growth of α' martensite reduce the plasticity of the material. Abstract: AISI 321 stainless steel is widely used in hydrogenation refining pipes and hydrogen storage vessel and so on owing to its excellent performance of creep stress resistance and high-temperature resistance. In this study, slow strain rate tensile tests (SSRT) were conducted under the condition of electrolytic hydrogen charging (EHC). The hydrogen embrittlement mechanism of AISI 321 stainless steel was analyzed in detail by means of scanning electron microscopy(SEM), X-ray diffraction spectrometer (XRD) and transmission electron microscope (TEM). The results show that hydrogen can change the fracture mode of tensile specimens from ductile fracture to brittle fracture mode. The main reason is that dislocations slide carrying hydrogen continuously in the material under the action of slow strain rate stress, resulting hydrogen cracks are preferentially produced at austenite grain boundaries, inclusions and the interface between δ ferrite and austenite. Additionally, it is easy to induce the transformation and growth of α' martensite in the process of hydrogen charging and reduce the plasticity of the material.